The More Education Program as a Comprehensive Education Policy: A literature review (Research, Society and Development, 2021)
This article is the partial result of a master's thesis that integrates the research developed at PPGE-UFOPA, focusing on the inducing policy of Integral Education, implemented through the Mais Educação Program (PME). The research aimed to conduct a literature review on the topic, addressing the theme Integral Education, Full-Time Education and the Mais Educação Program as a national policy in the context of Integral Education. It addresses the entire process of building the Policy, considering the regulations, the socioeconomic and political context in force in Brazil at the time, such as, for example, conditions of poverty and social exclusion and the implementation of the Program in schools that showed low performance in IDEB. The information served as a basis for analyzing and interpreting the contradictions that existed during the implementation of the More Education Program in the school context and, based on that, to promote discussions on integral education as a possibility to improve the quality of education in the Brazilian context, with specificities in the context of the Brazilian Amazon. The research, in addition to contributing to the existing theoretical framework, allows the reader to reflect on how the PME was implemented in schools that did not always offer physical and pedagogical conditions to carry out the proposed activities. Additionally, the study allowed us to infer on the need for a more consistent comprehensive education policy, as a fundamental element to improve the quality of basic education.